Effects of Breakpoint Changes on Carbapenem Susceptibility Rates ofEnterobacteriaceae: Results from the SENTRY Antimicrobial Surveillance Program, United States, 2008 to 2012 - Robert P Rennie; Ronald N Jones (Canadian Journal of Infectious Diseases and Medical Microbiology)
In the absence of clinical resistance, breakpoints for many antimicrobial agents are often set high. Clinical failures following use of the agents over time requires re-evaluation of breakpoints. This is based on patient response, pharmacokinetic/pharmacodynamic information and in vitro minimal inhibitory concentration data. Data from the SENTRY Antimicrobial Surveillance Program has shown that Clinical and Laboratory Standards Institute breakpoint changes for carbapenems that occurred between 2008 and 2012 in North America have resulted in decreased levels of susceptibility for some species. In particular, reduced susceptibility to imipenem was observed for Proteus mirabilis (35%) and Morganella morganii (80%). Minor decreases in susceptibility were also noted for Enterobacter species with ertapenem (5%) and imipenem (4.3%), and Serratia species with imipenem (6.4%). No significant decreases in susceptibility were observed for meropenem following the breakpoint changes. There were no earlier breakpoints established for doripenem. Very few of these Enterobacteriaceae produce carbapenamase enzymes; therefore, the clinical significance of these changes has not yet been clearly determined. In conclusion, ongoing surveillance studies with in vitro minimum inhibitory concentration data are essential in predicting the need for breakpoint changes and in identifying the impact of such changes on the percent susceptibility of different species.